2020
DOI: 10.2196/17526
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Effects of Usage of an Online Mindfulness Intervention for Distressed Cancer Patients: Usability Study

Abstract: Background One in three cancer patients experience high psychological distress. Mindfulness-based interventions are effective in reducing psychological distress in this patient group. However, these interventions lack availability and flexibility, which may compromise participation in the intervention for cancer patients experiencing late symptoms like fatigue or pain. Therefore, mindfulness-based interventions are increasingly offered via the internet. However, little is known about the usage of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 52 publications
3
25
0
1
Order By: Relevance
“…Our findings also indicated that education level does not predict the use of other sleep management strategies that we asked (sleep medication, CBT, mindfulness, hypnosis, acupuncture). These results are similar to the findings from studies in other cancer populations, for example on the use of mindfulness [37,38] and acupuncture [39] in cancer care. However, our data on sleep medication use differs from the findings in the general population, where sleep medication users are more likely to be of lower education than non-users [40,41].…”
Section: Sleep Management Strategiessupporting
confidence: 87%
“…Our findings also indicated that education level does not predict the use of other sleep management strategies that we asked (sleep medication, CBT, mindfulness, hypnosis, acupuncture). These results are similar to the findings from studies in other cancer populations, for example on the use of mindfulness [37,38] and acupuncture [39] in cancer care. However, our data on sleep medication use differs from the findings in the general population, where sleep medication users are more likely to be of lower education than non-users [40,41].…”
Section: Sleep Management Strategiessupporting
confidence: 87%
“…Of these, nine reported a positive association between engagement and mental health outcomes (33, 34, 36, 39-41, 43, 47, 49) while eight did not find a significant association (35,37,38,42,(44)(45)(46)48). Fourteen studies examined DMHIs that were guided (20,(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). Among these studies, six reported a positive association between engagement and mental health outcomes (50-52, 54, 55, 57) while eight did not find a significant association (20,53,56,(58)(59)(60)(61)(62).…”
Section: Unguided Vs Guided Interventionsmentioning
confidence: 99%
“…In the remaining 23 studies, participants were not formally diagnosed with a mental health condition but were screened for symptoms indicative of mental disorders. Of these studies, 12 reported a positive association between engagement and the primary mental health outcome (33,36,40,41,43,47,49,50,52,57,63,65) while the other 11 did not find a significant association (37, 38, 42, 44-46, 48, 58, 59, 62, 64).…”
Section: Mental Health Diagnostic Statusmentioning
confidence: 99%
“…Nine studies (35,36,42,44,46,50,52,59,64) investigated the relationship between engagement and psychological distress or psychological recovery. Of these, three reported a positive association between engagement and post-intervention symptoms (36, 50, 52) while six did not find any significant association (35,42,44,46,59,64).…”
Section: Psychological Distressmentioning
confidence: 99%
See 1 more Smart Citation